The dialogic mise-en-scène in The Land of Wandering Souls, by Rithy Panh (Comunicação & Inovação, 2023)
This paper analyzes the film The Land of Wandering Souls (2000), by Rithy Panh, from the hypothesis that its procedures outline a form of mise-en-scène that will later be central to the dispositive of S-21: The Khmer Rouge Killing Machine (2002). In both films, Panh gives space for the filmed to create their own staging and also intervenes in the scene, making the relationship between the filmmaker and the filmed a place for experimentation that produces questions and effects within the filmmaking process that will take the form of the dialogic mise-en-scène.
Keywords: documentary film; mise-en-scène; Rithy Panh